1994
DOI: 10.1002/jmv.1890440206
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of hepatitis B vaccines in neonates

Abstract: A literature search was carried out to investigate the factors that influence the protective efficacy (PE) of hepatitis B vaccines when given to neonates of hepatitis B surface antigen and e antigen positive mothers. Hepatitis B vaccines with either high or low antigen doses are very effective in preventing chronic hepatitis B infection in neonates at risk, but there is evidence that with lower dosages simultaneous use of hepatitis B immune globulin (HBIG) administration is more important than with higher dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(70 citation statements)
references
References 28 publications
0
66
0
4
Order By: Relevance
“…6,7 For infants born to HBsAg-positive women, immunoprophylaxis is reported to be 85% to 95% effective in preventing perinatally acquired chronic HBV infection. 8,9 The Advisory Committee on Immunization Practices (ACIP) recommends immunoprophylaxis consisting of hepatitis B (HepB) vaccine and hepatitis B immune globulin (HBIG) within 12 hours of birth, followed by completion of a HepB vaccine series ($3 doses for infants with a birth weight $2000 g; $4 doses for infants with a birth weight ,2000 g), and postvaccination serologic testing for vaccine-induced antibody and HBV infection. 8 Through grants to public health immunization programs, US Perinatal Hepatitis B Prevention Programs (PHBPPs) were created by the Centers for Disease Control and Prevention (CDC) in 1990 to accelerate progress toward elimination of perinatal HBV infection.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…6,7 For infants born to HBsAg-positive women, immunoprophylaxis is reported to be 85% to 95% effective in preventing perinatally acquired chronic HBV infection. 8,9 The Advisory Committee on Immunization Practices (ACIP) recommends immunoprophylaxis consisting of hepatitis B (HepB) vaccine and hepatitis B immune globulin (HBIG) within 12 hours of birth, followed by completion of a HepB vaccine series ($3 doses for infants with a birth weight $2000 g; $4 doses for infants with a birth weight ,2000 g), and postvaccination serologic testing for vaccine-induced antibody and HBV infection. 8 Through grants to public health immunization programs, US Perinatal Hepatitis B Prevention Programs (PHBPPs) were created by the Centers for Disease Control and Prevention (CDC) in 1990 to accelerate progress toward elimination of perinatal HBV infection.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…101 Passive-active immunization with HBV vaccine and HBIg administered 12-24 h after birth, followed by completion of a 3-dose vaccine series, has been demonstrated to be 85%-95% effective in preventing acute and chronic HBV infection in infants born to women who are positive for both HBsAg and HBeAg. 102 Although clinical trials have evaluated the efficacy of passive-active immunization with HBV vaccine and HBIg administered only within 24 h of birth, studies of passive immunoprophylaxis have demonstrated that HBIg provided protection when administered as late as 72 h after exposure. Infants born to HBsAg-positive/ HBeAg-negative mothers who receive passive-active immunization with HBIg and HBV vaccine are expected to should have the same high degree of protection as infants born to women who are HBsAg positive/HBeAg positive.…”
Section: Postnatal (Postpartum) Stage Interventions Immunizationmentioning
confidence: 99%
“…Ten to twenty percent of neonates born to HBsAg-positive mothers and 90% of those born to both HBsAg and HBeAg-positive mothers will be infected with HBV [10,11]. Immunization with hepatitis B immunoglobulin G (HBIG) and vaccine, administered at birth, reduces the risk of transmission to less than 10% among infants of mothers who are positive to HBsAg or HBeAg [12,13] however this is not yet the practiced in many hospitals in Nigeria. Studies from different parts of Nigeria have reported varying prevalence rates of HBV among different groups [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%